A study of volcanic rocks and ferromanganese crusts through marine geophysical methods integration in the north portion of Cruzeiro do Sul Rift in the Rio Grande Rise - Sergipe, Paula Possamai; Louro, Vinicius; Marangoni, Yára Regina; de Moura, Denise Silva; Jovane, Luigi (Frontiers in Marine Science, 2023)
The Rio Grande Rise (RGR) is an extensive structural high located in the South Atlantic Ocean, target of increasing exploratory interest. During the last decades, considerable attention has been given to its genesis, dynamic, regional tectonic, and composition. Some studies indicate the presence of volcanic rocks, mainly basaltic, related to their volcanic origin and Ferromanganese Crusts, boosting the research and economic interest. This study suggests the location of volcanic rocks and FeMn crusts at the north portion of Cruzeiro do Sul Rift within the RGR, characterizing the local geology and distribution pattern. We used multibeam bathymetry, sidescan sonar, dredges, and magnetic field data to integrate and better constrain the results. The magnetic field data highlighted the location of probable basaltic rocks, agreeing with the published literature, which was afterward confirmed by dredge samples. Their magnetic anomalies displayed the predominance of reverse polarization and less frequent normal polarization anomalies. FeMn crusts need a large volume of magnetite to cause anomalies in the local magnetic field, which does not happen in the RGR. There, they have reduced thickness and are frequently eroded, as displayed by the bathymetry, sidescan sonar, and geological data. Magnetic lineaments at the Rift margin defined a zone with a series of normal faults. During the Rift formation, transcurrent movements caused an intense fracturing, providing pathways for magma intrusion. Therefore, the fault zone could be related to the primary magnetic anomalies as a function of the magma intrusion and the occurrence of the rifting process and seafloor spreading. The new data presented in this paper brings valuable data for the comprehension and exploration effort of the RGR.